Penguatan Literasi Sains dan Karakter Peduli Lingkungan melalui Pendampingan Media Pembelajaran Berbasis Biodiversitas Lokal - Mahwar Qurbaniah; Mia Audina; Ahmad Faisal Amri; Nuri Dewi Muldayanti; Arif Didik Kurniawan (BALE LITERASI, 2026)
This community service program aimed to strengthen students’ scientific literacy and environmental awareness through biodiversity-based learning assistance at SMP IT Az-Zahira Khatulistiwa. The identified problems included the limited use of the school environment as a contextual learning resource, the lack of exploratory learning activities in science classes, and the limited utilization of local potential based learning media. The program employed a participatory experiential learning approach consisting of needs assessment, local flora exploration, learning media assistance, contextual learning implementation, and evaluation. Teachers and students actively participated in observing local plants, identifying plant characteristics, compiling flora identification sheets, and developing simple biodiversity-based learning media. The results demonstrated improvements in students’ scientific observation skills, plant classification abilities, collaborative learning, and environmental awareness. The program also produced local biodiversity learning media and an environmental education corner utilized as a sustainable science learning resource. Overall, the program contributed to the development of contextual, participatory, and environmentally oriented science learning.